Patients with colorectal cancer combined with HIV had a worse overall survival after surgery: a meta-analysis - Yang, Wen-Wen; Zhou, Xiong; He, Gan (Frontiers in Oncology, 2025)
PurposeThe purpose of this current study was to find out whether human immunodeficiency virus (HIV) affected overall survival (OS) of colorectal cancer (CRC) patients after surgery.MethodsPubMed, Embase, the Cochrane Library, and CNKI were searched from inception to March 27, 2023 to find eligible studies. Eligible studies included CRC patients grouped by HIV status (HIV-positive and HIV-negative). Stata SE 16 was used for data analysis.ResultsA total of eight studies involving 2180 patients were enrolled in this study. After data analysis, there were significant differences in sex (OR=0.69, 95% CI=0.49 to 0.98, I2 = 22.6%, P=0.04<0.1), tumor grade (OR=6.61, 95% CI=2.36 to 18.49, I2 = 0.00%, P=0.00<0.1), and tumor location (OR=2.19, 95% CI=1.74 to 2.77, I2 = 0.04%, P=0.00<0.1) between the HIV and non-HIV groups. Furthermore, we found that HIV was associated with worse OS in CRC patients after surgery (HR=3.12, 95% CI=2.07 to 4.69, I2 = 52.51%, P=0.00<0.1).ConclusionThis study highlights that HIV is associated with significantly poorer OS in CRC patients after surgery, emphasizing the need for tailored postoperative management strategies for this vulnerable population. Future research should explore underlying mechanisms and potential interventions to improve outcomes for HIV-positive CRC patients.